First-line pembrolizumab in advanced non–small cell lung cancer patients with poor performance status. (May 2020) - Facchinetti, Francesco; Mazzaschi, Giulia; Barbieri, Fausto; Passiglia, Francesco; Mazzoni, Francesca; Berardi, Rossana; Proto, Claudia; Cecere, Fabiana Letizia; Pilotto, Sara; Scotti, Vieri; Rossi, Sabrina; Del Conte, Alessandro; et al.
Abstract: Background: Pembrolizumab is the first-line standard of care for advanced non–small cell lung cancer (NSCLC) with a PD-L1 tumour proportion score (TPS) ≥ 50%. Eastern Cooperative Oncology Group performance status (PS) 2 patients may receive pembrolizumab, despite the absence of sustaining evidence. Patients and methods: GOIRC-2018-01 is a multicentre, retrospective, observational study. PS 2 NSCLC patients with a PD-L1 TPS ≥50% receiving first-line pembrolizumab from June 2017 to December 2018 at 21 Italian institutions were included. Clinical-pathological characteristics were correlated with disease response and survival outcomes; adverse events were recorded. The primary objective was 6-months progression-free rate (6-months PFR). Results: One hundred fifty-three patients (median age 70 years) were enrolled. At a median follow-up of 18.2 months, median progression-free survival (PFS) and overall survival (OS) were 2.4 (95% confidence interval, 95% CI, 1.6–2.5) and 3.0 months (95% CI 2.4–3.5), respectively. 6-months PFR was 27% (95% CI 21–35%). Patients with a PS 2 determined by comorbidities (n = 41) had significantly better outcomes compared with disease burden-induced PS 2 (n = 112). Indeed, 6-months PFR was 49% versus 19%, median PFS 5.6 versus 1.8 months and OS 11.8 versus 2.8 months, respectively. Additional potential prognostic factors (radiotherapy, antibiotics, steroids received before pembrolizumab) correlated with clinical outcomes. The determinant of PS 2 resulted the only factor independently impacting on both PFS and OS. No toxicity issues emerged. Conclusions: Outcomes of PS 2 NSCLC patients with PD-L1 TPS ≥50% receiving first-line pembrolizumab were globally dismal but strongly dependent on the reason conditioning the poor PS itself. Highlights: Evidence on first-line pembrolizumab in Eastern Cooperative Oncology Group performance status (PS) 2 non–small cell lung cancer (NSCLC) (PD-L1 ≥ 50%) are poor. This retrospective study documented dismal outcomes in this population of interest. Patients with disease burden-determined poor PS had poor prognosis. Comorbidity-induced PS 2 may still benefit form pembrolizumab. The differential determinants of PS 2 in NSCLC are relevant for clinical decisions.